Special aspects of 12-14 yrs children's psychological protection - V.M. Liashenko; V.M. Tumanova; N.P. Gnutova; E.I. Gnutov (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to analyze special aspects of 12-14 yrs children's psychological protection's manifestations. Material: In the research children of 12 years (n= 5), 13 years (n=7) and 14 years (n=13) participated. Results: The greatest quantity of correlations was observed between compensation and hyper-compensation with other kinds of psychological protection. It was found that projection is the most frequently used by children psychological protection mechanism. It is observed in 76.7% of children. Second place is taken by refusal (50.9%). On third place stands compensation (50%) and hyper-compensation (50%). The greatest quantity of interdependent correlations we received between compensation and other kinds of psychological protection (5 correlations) and projection (4 correlations). Conclusions: Children's behavior can be regarded from the point of their emotional sphere, conscious and not conscious behavioral manifestations of this sphere. We give information to school psychologists about psychological everyday state of children. This information will help to understand the reason of de-adaptation or difficulties' emersion in children's life as well as permit to find appropriate means of work with problems and their correction.